Managerial Competencies in Educational Institution (Docentes 2.0 Journal, 2024)
Globally, the effects of the pandemic in the field of education have reached a crisis level. The objective of the research was to conduct a systematic review of managerial competencies in educational institutions in Latin America. It was based on a systematic literature review, analytical method, positivist paradigm with a quantitative approach, and descriptive type based on a meta-analysis. The sample consisted of fifteen articles (n=15) selected from the main search engines, such as Scielo, Latindex, and Dialnet, during 2019-2023, according to the inclusion criteria established and arranged following the PRISMA protocol. The results showed a wide scientific production in 2022, coming from the Dialnet database, in social sciences, and mainly from Peru. In conclusion, effective managerial competencies are crucial for the success of any educational institution. Therefore, any orientation and subsequent actions of managers in the institution should focus on their effectiveness and dedication in promoting strategic thinking, learning management, teamwork, and interpersonal connections.
Keywords: Competencies; managerial leadership; pedagogical management; institutional climate; educational quality